2020
DOI: 10.1002/brb3.1753
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐cultural differences in Parkinson's disease caregiving and burden between the United States and Mexico

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 43 publications
(62 reference statements)
1
13
0
Order By: Relevance
“…PD caregivers in Mexico and the US. A more detailed comparison of Mexican and US PD caregiver and patient characteristics such as education, social class, and caregiving-related variables is outlined in another manuscript [24], which found that caregivers at the US site were older than those in Mexico, had higher education and social class, and spent fewer hours per week providing care.…”
Section: Procedure Following Protocol Review and Approval Bymentioning
confidence: 99%
“…PD caregivers in Mexico and the US. A more detailed comparison of Mexican and US PD caregiver and patient characteristics such as education, social class, and caregiving-related variables is outlined in another manuscript [24], which found that caregivers at the US site were older than those in Mexico, had higher education and social class, and spent fewer hours per week providing care.…”
Section: Procedure Following Protocol Review and Approval Bymentioning
confidence: 99%
“…One explanation for the regional variation observed in this study could involve cultural factors related to patient self‐perception, use of healthcare resources, caregiving, and treatment practices for patients with PD. Findings from studies have shown intercountry differences in caregiver demographics, the amount of burden, and time spent caregiving, possibly because of differences in the availability of social support and cultural attitudes toward familial caregiving 16,17 . Likewise, cultural differences have been attributed to different outcomes in cognitive testing 18 .…”
Section: Discussionmentioning
confidence: 99%
“…There is some evidence for interventions to reduce caregiver strain which include education for the person with PD and the caregiver, psychotherapy targeting psychiatric symptoms in the caregiver and management of neuropsychiatric symptoms in the person living with PD [ 22 ]. Lastly, caregiver strain is influenced by cultural perceptions of disease and caregiving, leading to different results in other parts of the world [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%